HISTORY OF TASHKENT OASIS REFLECTED IN ROCK PICTURES - Abdurakhmonova Jummagul Namozovna (Western European Studies, 2024)
The article describes the study of rock paintings found in Tashkent region as a historical material culture, the chronology and content of these rock monuments, the uniqueness of rock paintings. At the same time, the role and importance of rock paintings in the history of the Tashkent oasis is highlighted in the article.
Keywords: Types of ancient art; material wealth; rock paintings